2010
DOI: 10.5762/kais.2010.11.3.1126
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Health Promotion Behavior of Shifting Nurses' on the Health Conditions

Abstract: The purpose of this research was to analyze the health promotion behavior of shifting nurses' and its effects on their health conditions. The survey was performed for 357 nurses who worked in general hospital during July 2006. The results for behavior of health promotion and health conditions were as follow; Better health conditions of shifting nurses' on the aspects of physical status, the younger age, a fewer night duties in a month, more regular menstruation cycles and married rather than un-married, they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…A study on shift-work nurses also reported similar results [44]. In the case of married people, domestic stability has a positive effect on their work [45]. They also have more people to provide social support and are more responsible for their health due to factors such as pregnancy, childbirth, and childcare, resulting in them expending more effort into health promotion behavior.…”
Section: Discussionmentioning
confidence: 73%
“…A study on shift-work nurses also reported similar results [44]. In the case of married people, domestic stability has a positive effect on their work [45]. They also have more people to provide social support and are more responsible for their health due to factors such as pregnancy, childbirth, and childcare, resulting in them expending more effort into health promotion behavior.…”
Section: Discussionmentioning
confidence: 73%
“…With respect to gender, the studied sampled are formed from the two groups of males and females identically, Age groups shows that about half of the studied subjects at the last two age groups, since they are accounted 60(47.3%), this result was consistent with the study in which the researcher found that the mean of age of the participants was 40-49 years (17) , body mass index shows about two third of the studied subjects having an overweight, Most studied nurses were recorded their educational levels at the diploma, or less, and are accounted 107(94.5%), then finally occupational years are formed identical distribution along different groups.Table (2):Results shows that highly significant differences are accounted at P<0.01 among the observed distribution with their an expected outcomes. With respect to "Health Promotion Training", two third of the studied sampled are assigned a health promotion training, since they are accounted 83(65.4%), and among who had training courses, and only 15(13.3%) of the studied sampled had smoking soon, and hooking, and no one among the studied sampled drinking alcoholic, and finally, two third of the studied nurses are assigned exercising, and they are accounted 85(66.9%), Also, the study findings agree with study of that show the majority of participants never smoking, drinking and practice physical activity (1-2) times per week (18) .Figure (1) represent "Percentile Grand Mean of Score" values, as well as an overall evaluation to main domains of studied nurse's responding, In study that depict that the majority of main (83.34%) and family medicine (100%) primary health care centers have good overall evaluation (19) .In table (3), which consists of contingency coefficients for testing the statistical hypothesis, which says that no relationships are accounted between redistribution of preceding variables.Table (4) shows in term of simple correlation coefficients (Person's correlation coefficients) among studied main domains. There an inclusive significant relationships at P<0.01for the extracted correlation coefficients among all studied main domain's pairwise, and that interpreting appearance a unique of extracted factor (The Covariance) (20) .…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide clients with the outcomes they want, good quality clinical care is essential, and nurse performance evaluation is a key component of that (1,2) .The term "role model" evoked a variety of interpretations among the nurses, ranging from negative perceptions of the idealized image to a more humanized and authentic representation. Nurses defined themselves as role models of health promotion based on the meaning they gave the term, their perceptions of societal expectations, and the selfconstructed personal and professional domains (3,4) .Since nurses serve as role models for their patients, they have a significant influence on both their own and their patients' lifestyles (5) .WHO defines health promotion as the act of empowering people by increasing the control they have over their own health. Health promotion encompasses a wide range of social and environmental interventions designed to benefit and protect individuals' health and quality of life by addressing and preventing the underlying causes of ill health, rather than merely concentrating on treatment and healing (6,7) .Primary health care (PHC) focuses on the public's demands for a sustainable healthy existence without placing any financial burden on patients in order to ensure the maximum degree of health and well-being and their equitable distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire consisted of questions spanning five sections: • Healthy behaviors Healthy behaviors were measured using the nurses' health promoting behavior scale developed by Kim et al [23]. The scale consists of 16 items with 5 subscales: self-concept as a nurse (2 items), management of work life (4 items), healthy lifestyle (5 items), stress management (3 items), and interpersonal relationships in the workplace (2 items).…”
Section: Measurementsmentioning
confidence: 99%